HVEM HAR ANSVARET? En immigrantfamilies møde med den danske institutionsverden - Bundgaard, Helle (Tidsskriftet Antropologi, 2002)
The article presents an experience near analysis of events, which took place in connection with an immigrant child’s start in a Danish pre-school. More specifically it deals with the inter-subjective meetings between the mother of the child and preschool staff. The analysis raises questions regarding Danish cultural assumptions about the appropriate relation between children and responsibility as well as the inviolability of the nuclear family.The Danish cultural conception of the integrity of the individual and family means that pre-school staff generally tries to solve problems themselves or call on professional assistance. Due to fear of mixing distinct life worlds, the staff will not contact members of a family network or other people with whom a parent shares mother tongue in order to solve a problem. This principle does indeed safeguard against undesirable interference, but it simultaneously cuts off relations, which in certain situations might have helped reaching a meaningful contact.